2008
DOI: 10.1021/cg8006525
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Growth and Orientation of Sm−Ba−Cu−O Phases on a Sm-211 Whisker Substrate by High-Temperature Optical Microscopy

Abstract: Formation of various Sm-Ba-Cu-O phases grown under thermal equilibrium on (010) surfaces of Sm 2 BaCuO 5 single-crystalline whiskers was observed in situ by means of a high-temperature optical microscope. At 1100°C a needle-like phase, identified by X-ray diffraction and energy-dispersive spectroscopy analyses as Sm 2 Ba 4 Cu 2 O y , grew epitaxially on the whisker (010) surface. After being cooled to 1050°C (close to the peritectic temperature, T p ), the SmBa 2 Cu 3 O y (Sm-123) phase nucleated and grew epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…A primary study was conducted on the effect of Sm242 addition on the microstructure and superconducting properties of airprocessed Sm123 samples. In addition, in our previous work [19], we found that both Sm123 and Sm242 phases present an epitaxial relationship with the Sm211 phase. Further, it was deduced that there might be an epitaxial relationship between Sm123 and Sm242, too.…”
Section: Introductionmentioning
confidence: 49%
“…A primary study was conducted on the effect of Sm242 addition on the microstructure and superconducting properties of airprocessed Sm123 samples. In addition, in our previous work [19], we found that both Sm123 and Sm242 phases present an epitaxial relationship with the Sm211 phase. Further, it was deduced that there might be an epitaxial relationship between Sm123 and Sm242, too.…”
Section: Introductionmentioning
confidence: 49%
“…Secondly, people in the north who are fat are more likely to suffer from nonalcoholic fatty liver than other populations, the study didn't do liver biopsy, so the non-alcoholic fatty liver which can not be identified is regarded as alcoholic liver disease according to alcohol consumption. Thirdly, in recent years, the production and consumption of alcohol in China increased as a result of the rapid social and economic changes (Hao et al, 2004;Kim et al, 2008;Zhou et al, 2009). Previously reported prevalence of ALD were out of date, which do not represent population data.…”
Section: Discussionmentioning
confidence: 97%